Política pública para o idoso : um estudo da cidadania no Grupo Cabelos de Neve do Programa Conviver em Campina Grande-PB - Marques, Robson Oliveira (2010)
The main objective of the study about the citizenship development in elderly attended by the Conviver Program of the City Hall of Campina Grande in Paraiba, Brazil was to evaluate how the actions of the Program contribute for the citizenship practice according to the users. The Citizenship analyzed is the existence of political, civil and social rights according to Marshall. For that it was utilized a descriptive research and a study of case based on technical procedure. The research was settled by the people who are benefited by the Conviver Program of the Snow Hair Group and the sample was formed by the active participants that it is in the Group for over ten years, corresponding to a total of ten elderly. For the data collection was utilized basic questionnaire in function of the low schooling of the interviewed, according to Marshall (2002) theory about the citizenship construction from each person. It was utilized the methodological procedure proposed by Bardin (2006), categorical analysis, in the qualitative data analysis, that was divided in four parts. In relation to Political Rights, noted that the program has stimulated your Watched on the exercise of voting and being voted. On the Civil Rights was observed that the Program has given incentive to actions which provide the users the justice rights in and in occupational activities as a job. In relation to Social Rights it was observed that the Conviver Program has contributed in order that its users can lead their lives according to the standards imposed by the society, which have being failed in the education area. As for the type of citizenship it was verified that the Program has given incentive to the served users, becoming more evidence on the speech basis